The control system design and study for continuous supersonic wind tunnel - CHEN Dan (Xibei Gongye Daxue Xuebao, 2022)
As the first continuous supersonic wind tunnel in China, Mach number and total pressure are the most important flow field parameters of the wind tunnel, how to precise control and rapid and stable adjustment of total pressure and Mach number is the key in the design and construction of the wind tunnel control system. By analyzing the principle of parameter control of the wind tunnel flow field and the coupling relationship of each adjustment methods, the construction of continuous supersonic wind tunnel control system is constructed, and the solution measure of each key technical problem is given. The total pressure is precisely controlled by the segmented variable parameter fuzzy PI control algorithm, and then the wind tunnel operation control process design is carried out. Finally the wind tunnel blowing test is verified. The result shows that the accuracy of total pressure accuracy is better than 0.05%, the Mach number accuracy is better than 0.167 3, all the flow field parameter is greatly better than the design index, which proves that the design idea proposed in this paper is effective and can provide reference for the design and debugging of continuous supersonic wind tunnels.